The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1242/dev.096933
|View full text |Cite
|
Sign up to set email alerts
|

Sdc2 and Tbx16 regulate Fgf2-dependent epithelial cell morphogenesis in the ciliated organ of asymmetry

Abstract: SUMMARYHeparan sulfate proteoglycans (HSPGs) control many cellular processes and have been implicated in the regulation of left-right (LR) development by as yet unknown mechanisms. Using lineage-targeted knockdowns, we found that the transmembrane HSPG Syndecan 2 (Sdc2) regulates LR patterning through cell-autonomous functions in the zebrafish ciliated organ of asymmetry, Kupffer's vesicle (KV), including regulation of cell proliferation and adhesion, cilia length and asymmetric fluid flow. Exploring downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The number of KV cells can be variable among wild-type embryos, but the nature of this variation remains unclear. Previous studies have identified roles for Syndecan 2 (Arrington et al, 2013), and β-catenin, (Zhang et al, 2012), in DFC/KV cell proliferation during somite stages, but regulators of DFC proliferation during epiboly have not been identified. A roadblock to understanding DFC/KV cell proliferation has been the lack of a comprehensive census of the DFC/KV cell population during their development.…”
Section: Discussionmentioning
confidence: 99%
“…The number of KV cells can be variable among wild-type embryos, but the nature of this variation remains unclear. Previous studies have identified roles for Syndecan 2 (Arrington et al, 2013), and β-catenin, (Zhang et al, 2012), in DFC/KV cell proliferation during somite stages, but regulators of DFC proliferation during epiboly have not been identified. A roadblock to understanding DFC/KV cell proliferation has been the lack of a comprehensive census of the DFC/KV cell population during their development.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that early developmental events generate LR positional information that can be used to guide ciliated cells as they develop into a functional LRO or to completely bypass the requirement for cilia [93,94]. Several connections have been made between molecules involved in early LR events and the development of the LRO: Syndecan 2 [95] and the vacuolar-type H þ -ATPase [88,96,97] are involved in the development of normal LRO morphogenesis and cilia formation in zebrafish, and H þ / K þ -ATPase activity [98] and serotonin [99] are needed for Wnt signalling pathways that control LRO development and ciliogenesis in frog embryos. One outstanding question is whether precursor cells receive laterality cues prior to forming the LRO.…”
Section: (C) Laterality Cues For Cilia?mentioning
confidence: 99%
“…Although Syndecan-2 is presumed to regulate inside-out signaling between adjacent cells, it is also possible that it has a direct effect on intracellular interactions, as phosphorylation of Syndecan-2's intracellular domain on the right side of the embryo is essential for asymmetric gene expression and morphogenesis . In zebrafish, Syndecan-2 has a cell-autonomous role in the dorsal forerunner cells, which are the progenitors of Kupffer's vesicle, the zebrafish LRO (Arrington et al, 2013). Morpholino knockdown of Syndecan-2 prevents the dorsal forerunner cells from coalescing and adhering to one another, resulting in disrupted morphogenesis of Kupffer's vesicle.…”
Section: The Ecm: Force and Movementmentioning
confidence: 99%
“…Morpholino knockdown of Syndecan-2 prevents the dorsal forerunner cells from coalescing and adhering to one another, resulting in disrupted morphogenesis of Kupffer's vesicle. These fish have cilia defects that impact fluid flow and subsequently exhibit aberrant asymmetric gene expression in the lateral plate mesoderm (Arrington et al, 2013;Chen et al, 2004;). The Syndecan-2 morphants have decreased expression of Tbx16 and Fgf2 in the dorsal forerunner cells, leading to the suggestion that spatially and temporally-regulated patterns of glycosaminoglycan modifications of core ECM proteins may be responsible for cell-type-specific gene expression (Arrington et al, 2013).…”
Section: The Ecm: Force and Movementmentioning
confidence: 99%
See 1 more Smart Citation